2014
DOI: 10.1177/1740774513519876
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes toward clinical trials among patients with sickle cell disease

Abstract: Background A substantial number of planned clinical trials for sickle cell disease (SCD) have terminated early due to insufficient patient enrollment. Purpose To describe attitudes towards clinical trials among a sample of adults with SCD and identify patient-level factors associated with these attitudes. Methods Our data came from a sample [N = 291] of primarily adults with SCD participating in the Improving Patient Outcomes with Respect and Trust (IMPORT) study, which is a federally-funded observational … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
20
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 28 publications
2
20
0
Order By: Relevance
“…[30][31][32] Historically, African Americans have been reported to have a distrust of the medical community in general, and clinical trials, in particular. 33 Haywood et al 34 report changing attitudes among SCD patients about participation in clinical trials. In their study, more education, better-perceived health status, and previous clinical trial participation were all associated with more positive attitudes about clinical trials.…”
Section: Discussionmentioning
confidence: 99%
“…[30][31][32] Historically, African Americans have been reported to have a distrust of the medical community in general, and clinical trials, in particular. 33 Haywood et al 34 report changing attitudes among SCD patients about participation in clinical trials. In their study, more education, better-perceived health status, and previous clinical trial participation were all associated with more positive attitudes about clinical trials.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, acceptance of the optional banking of DNA for future genetic studies has been remarkably high (97.9%). Research study acceptance and enrollment have been traditionally low for SCD, [60][61][62][63][64][65] and some reports have indicated that African Americans are less likely than other racial and ethnic groups to support genetic studies that require a broad consent for the use of biospecimens in genetics research. 66,67 We attribute our high rate of enrollment to the possible benefit of genetic studies perceived by our patient population.…”
Section: Discussionmentioning
confidence: 99%
“…The SWIM trial had difficulties in patient recruitment and, as a result, was terminated early. Other trials in patients with sickle cell disease have faced similar issues in recruitment, and many have also terminated early [ 5 ].…”
Section: Methodsmentioning
confidence: 99%
“…Finally, it can adversely impact the feasibility of conducting trials for conditions with a small patient pool. For example, a number of trials in patients with sickle cell disease have been terminated early due to insufficient recruitment [ 5 ]. As a result, care for patients with less common conditions may be based on suboptimal evidence from underpowered trials or non-randomised studies.…”
Section: Introductionmentioning
confidence: 99%